Police ethics and integrity: Keeping the ‘blue code’ of silence - Conway, Steve (2020)
This paper examines attitudes towards police ethics and integrity using the responses of police officers and support staff to some ethical dilemmas via an online questionnaire. The aim of the study was to explore potential connections between respondents’ beliefs about the seriousness or type of misdemeanour and their likelihood of reporting the behaviour. Using a series of scenarios, we explore professional ethics and integrity by analysing the evidence from our survey of around 1,500 police officers, police community support officers (PCSOs) and police support staff. Throughout, we aim to show which of the scenarios were considered the most ‘serious’, which are more likely to be reported, and offer some suggestions as to why the ‘blue code’ is significant. The findings suggest the persistence of a reluctance to report some misdemeanours; of the 10 scenarios created for the survey, there was a great deal of certainty around the reporting theft of cash, but respondents were less likely to report a colleague keeping a ‘found’ watch. Accessing the Police National Computer without due authority was seen as relatively ‘serious’ and covering up for a drink-driving colleague and use of excessive force were both likely to be reported. We discovered ambiguities in responses around sexual touching of a colleague in an office setting, but a lower level of concern regarding an officer who forms a romantic relationship with a victim of crime who he met in a professional setting. Respondents expressed distrust in the force’s anonymous messenger system, set up for reporting a colleague’s behaviour without revealing their own identity and said they could treat a whistle-blower with respect or caution, depending on the circumstances of the individual case